"Describing Misbehaviour in Vung Tau as 'Mischief' Is Ridiculously Coy": Ethnographic Refusal, Reticence, and the Oral Historian's Dilemma. (1st April 2018) - Riseman, Noah
Abstract: Since 2009 I have been part of three projects examining the history of service in the Australian military of Aboriginal and Torres Strait Islander people, as well as people who identify as lesbian, gay, bisexual, transgender, and intersex (LGBTI). The oral histories of these current and ex-service personnel contain tales that include family violence (both as perpetrators and survivors), war trauma, alcoholism, and sexual assault. There are also many silences, particularly among Vietnam veterans, when discussing misbehavior on rest-and-convalescence leave in the Vietnamese coastal town of Vung Tau. In this article, I explore some of the ways that I have navigated the ethical dilemmas of writing these histories, referring in particular to how the concepts of ethnographic refusal and reticence have influenced my practice. I argue that interviewers need to be cautious when confronting participants' reticence to engage with particular lines of questioning. Researchers must consider the wider social, political, and personal implications of their research for their narrators and decide whether ethnographic refusal—avoiding the subject matter to protect the interviewees—is an appropriate strategy.